2004
DOI: 10.1038/sj.bmt.1704641
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-lymphoma effect in refractory cutaneous T-cell lymphoma after reduced-intensity HLA-matched sibling allogeneic stem cell transplantation

Abstract: Summary:Cutaneous T-cell lymphomas (CTCL) are rare diseases that, in their advanced stages or in transformation, have a poor prognosis. Autologous stem cell transplantation (Au-SCT) after high-dose therapy has yielded disappointing results. Allogeneic transplantation (allo-SCT) provides the potential advantage of an immune-mediated graftversus-lymphoma (GVL) effect. Reduced-intensity allo-SCT potentially offers a GVL effect, but with diminished toxicity related to the induction regimen; however, published expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…Similarly the suppressive effects of low dose cyclophosphamide or fludarabine on Treg cells might not selectively target Treg-like neoplastic T-cells vis-á-vis normal Treg cells [80][81][82]. At the present time, a non-myeloblative allogeneic bone marrow transplantation with the intent of generating a graft-versus-lymphoma effect may provide the best therapeutic option to gain long-term survival in these patients [83][84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly the suppressive effects of low dose cyclophosphamide or fludarabine on Treg cells might not selectively target Treg-like neoplastic T-cells vis-á-vis normal Treg cells [80][81][82]. At the present time, a non-myeloblative allogeneic bone marrow transplantation with the intent of generating a graft-versus-lymphoma effect may provide the best therapeutic option to gain long-term survival in these patients [83][84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are a number of reports of a GvLy effect for cutaneous T-cell lymphoma, and further investigation is warranted to establish if this effect extends to other PTCL. 23 One potential way to reduce the high transplant-related mortality rate would be to employ an RIC, which would facilitate engraftment as a platform upon which to develop the GvLy effect, including the programmed use of donor lymphocyte infusions. 19,24 Corradini et al 12 reported prospectively on 17 patients with relapsed/primary refractory T-cell lymphomas treated with RIC Allo-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…[104][105][106] Investigators have been evaluating reduced-intensity conditioning for MF/SS and transplantation-related mortality is low, time to relapse is variable, and durable remissions are observed. 107,108 We recommend that allogeneic transplantation be considered in younger patients with advanced-stage disease if not responding to agents such as IFN-␣, bexarotene, HDACi, or denileukin diftitox.…”
Section: Transplantationmentioning
confidence: 99%